EFEKTIVITAS TEKNIK RELAKSASI UNTUK MEREDUKSI KECEMASAN BERBICARA DI DEPAN UMUM SISWA SMPN 11 KOTA JAMBI - Dita Sephira Amalia; Muhammad Ferdiansyah; Rully Andi Yaksa (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research is entitled The Effectiveness of Relaxation Techniques for Reducing Anxiety Public Speaking for Students of SMPN 11 Jambi City. With the aim of find out whether relaxation techniques are effective in reducing speaking anxiety in public at SMPN 11 Jambi City students. This research is field research with quantitative methods used an experimental method with a two group pretest post test design This treatment was applied to 52 students, with a sample of 26 experimental group students and 26 control group students. Data analysis used the t test with the help of the SPSS version 26. The results of this research prove that the relaxation technique is effective in reducing students' anxiety about speaking in public and from significant grades (2tailed) of 0.003 < 0.05, it can be concluded that there is a decrease in the average after implementing relaxation techniques to reduce anxiety about speaking in front General Students of SMPN 11 Jambi City. Based on the research findings, it can be concluded that relaxation techniques effective for reducing students' anxiety levels about speaking in public SMPN 11 Jambi City. The implications of this research can be an illustration for teachers can provide relaxation techniques to reduce the level of speaking anxiety in public for students of SMPN 11 Jambi City.